The development of student worksheets using ethnomatematics based prediction, observation, and explanation learning models to improve student's critical thinking ability - Mania, Sitti; Jamaluddin, Nazurah; Kusumayanti, Andi; Nur, Fitriani (Universitas Islam Negeri Raden Intan Lampung, 2021)
This research is a research and development that aims to develop and assess the quality of student worksheets (LKPD) using ethnomathematics-based prediction, observation, and explanation (POE) learning models to improve students' mathematical critical thinking abilities that are valid, practical, and effective. This research is a development research that refers to the ADDIE development model, namely, analysis, design, development, implementation, and evaluation. In this research, the test subjects were students of class VIII G MTs Al-Urwatul Wutsqaa Sidrap Regency with 26 students. Based on the results of the trials that have been carried out, it is found that (a) The validation of LKPD and other instruments are 3.78 in the